Elongation exercises and the default way Albulayomterc and its impact on some of the capabilities Career and skill in volleyball - Noureddine Issa, Samah (Journal of Physical Education, 2012)
Is the exercise received by the student or trainee a priority task within the curriculum or teaching as it contains the characteristics of public and private took spread widely at the present time, and the possibility of these exercises on the development of functional capacity and skill if applied correctly and selected in a way serving the desired goal, with the goal of this research is to identify the effect of exercise (elongation and failure) on some functional capacity and skill in volleyball, and also to identify the effect of training method Albulayomterc on these capabilities. Where the researcher used the experimental method to fit the nature of the problem, and the sample was one of the students of the Faculty of Physical Education Phase II / Department of Teaching / and the number (20) students were distributed into two groups: control group and experimental rate of (10) students per group, the researcher concluded that the use of exercise for Balasttalh and the default way that training Albulayomterc have a positive effect, moral and this is shown by results between pre and post tests and in favor of the experimental group, which indicates the existence of a correlation between test results because the value of (t) calculated greater than the value spreadsheet, and the results showed also to improve the level of performance for the test results of functional test capabilities is the ability Alloxgenih Alphusvegeneh and Allakticah and also to test the skill of beating overwhelming and all results were significant.